The Impact of Body Fat Percentage towards the Attention Aspect of the Cognitive Function in Pre-Clinical University Students of Atma Jaya - Mariani Santosa; Alvin Edwin Wiyono; Robi Irawan (Fakultas Kedokteran Universitas Sriwijaya, 2021)
In 2016, World Health Organization (WHO) predicts that 650 million adults aged 18 and more have obesity. Many research shows that obesity affects brain function and impairs the cognitive function of the brain. To understand whether body fat percentage has an impact on the attention aspect of the cognitive function in university students. This study is a cross-sectional study approach. The data was collected from August 2020 until March 2021 with a total of 72 respondents. The data was collected using the body fat percentage formula from the British Journal of Nutrition to assess body fat percentage and Stroop Test for attention. Kruskal-Wallis and spearman were used to assess the correlation between body fat percentage and attention. The result shows that body fat percentage affects the attention aspect of the cognitive function (p = 0.001, r = 0.71). In conclusion, based on 72 university students, it proves that body fat percentage has an impact on the attention aspect of the cognitive function. The impact that high body fat percentage does is lowering the attention aspect of the cognitive function.